Humanism and Calvinism : Andrew Melville and the universities of Scotland, 1560-1625 - Reid, Steven J. (St. Andrews studies in Reformation history., 2011)
This book surveys the transformation of Scotland's medieval and Catholic university system into a greatly-expanded Protestant one in the decades following the Scottish Reformation of 1560. It also assesses the contribution of religious reformer Andrew Mel.